PENGARUH KEJELASAN SASARAN ANGGARAN TERHADAP SENJANGAN ANGGARAN PADA UIN SYARIF HIDAYATULLAH - Reskino Reskino; Wilda Farah (ETIKONOMI, 2012)
This research examines the effect budget goal clarity on UIN Syarif Hidayatullah Jakarta budgetary slack and tries to understand the influences of organizational commitment on the relation of budget goal clarity as well as UIN Syarif Hidayatullah Jakarta budgetary slack. The subjects of this study are structural functionary there are in Rectorat, Internal Audit Unit, eleven faculty, PostGraduate, Syahida Inn, general library of UIN Syarif hidayatullah Jakarta. The analysis method on this research is regression analysis. The results show that budget goal clarity were influenced by the local government institution’s budgetary slack. Then organizational commitment act as moderating variable in the relation of budget goal clarity with local government institution’s budgetary slack.DOI: 10.15408/etk.v11i1.1870